Bipolar-interface fuel cells – an underestimated membrane electrode assembly concept for PGM-free ORR catalysts. Issue 5 (26th March 2020) - Seeberger, Dominik; McLaughlin, David; Hauenstein, Pascal; Thiele, Simon
Abstract : We present the first combination of a bipolar interface fuel cell with a commercial Fe–N/C catalyst as an alkaline cathode and a PGM-based, acidic anode, both separated by a proton exchange membrane (PEM). Abstract : We present the first combination of a bipolar interface fuel cell with a commercial Fe–N/C catalyst as an alkaline cathode and a PGM-based, acidic anode, both separated by a proton exchange membrane (PEM). This membrane electrode assembly (MEA) concept enables the employment of Fe–N/C catalysts in a less corrosive alkaline environment, while simultaneously keeping the profound advantages of the hydrogen oxidation reaction in acidic media with extremely low PGM-material requirement. We compare two different cases for the anion exchange polymer–proton exchange polymer (AEM|PEM) interface at the alkaline cathode and the acidic membrane. In one case the PEM is simply pressed against the alkaline electrode and in the other case a part of the PEM is deposited onto the alkaline electrode. We achieved power densities of about 38 mW cm −2 and 210 mW cm −2 respectively. This is corresponding to 2.1 W mgPt −1 cm −2 . Our results show, that the bipolar interface design is one of the most important factors for performance optimization in BPM fuel cells. In addition, we compared a conventional PEM fuel cell with identical Fe–N/C cathode loading to the bipolar deposition case. After a 15 hour test run the PEMFC cell showed a strongly increased overpotential at lower current densities, whereas the overpotential increase for the bipolar cell was only marginally in the same current density region. With this work we show a facile manufacturing approach that enables bipolar interface fuel cells with Fe–N/C catalysts, showing promising power densities at low total PGM-loadings.